Out of hiding : extremist white supremacy and how it can be stopped - Blee, Kathleen M. 1953- (Routledge studies in extremism and democracy, 2024)
"Out of Hiding: Extremist White Supremacy and How It Can Be Stopped explains how white supremacist extremism endures, the varied forms it takes, its relationship to systemic racism, and what to do about it. The book draws on more than 30 years of extensive data and direct experiences with extremists to describe how white supremacy moved into the spotlight during the first two decades of the 21st century. The argument focuses on three moments between 2008 and today during which white supremacists took opportunities to move from pockets of underground activism to violent protests across the United States. The authors offer a corrective to observers who mischaracterize today's racial extremism as a new form of "alt-right" conservatism or "white nationalism" emanating from an isolated, poorly educated, economically disenfranchised online fringe. These misunderstandings reflect the limited attention given to the varied and persistent forms of racial extremism that have long simmered in America and an inability to acknowledge the appeal white supremacist messages can hold for a broad swath of the US population. This volume contributes a longer view than other books to demonstrate that today's white supremacy is less a unique eruption than a continuation - and an acceleration - of longstanding US white supremacy. This is essential reading for scholars and activists interested in racism, white supremacy, and far-right extremism"--